Study of the Interaction of Heavy Metals (Cu(II), Zn(II)) Ions with a Clay Soil of the Region of Naima-Tiaret-Algeria - Taibi Mohamed; Elaziouti Abdelkader; Laouedj Nadjia; Dellal Abdelkader (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
The RM (RM stands for the pristine clay) collected from sites in the Naima-Tiaret-Algeria and its purified phase TM (TM stands for the treated clay) were characterized using XRF, XRD, FT−IR, SEM−EDX, and DC electrical conductivity techniques. The as-prepared clays were used as potential adsorbents for the removal of Cu2+ and Zn2+ metals ions. Highly purified clay TM, exhibiting a basal, spacing of 25.83 Å and CEC of 51 meq/100 g, was obtained. The type of interstratified I/M in the studied sites is S=1, based on the calculation method of Watanabe. The percentage of illite type S=1 is between 80−85% illite. The adsorption equilibrium was established in 60 min with the capacities of 28.57 and 24.39 mg/g for Cu2+ onto RM, 32.25 and 4.95 mg/g for Zn2+ in the presence of TM. D-R isotherm model was more suitable with the adsorption process than Freundlich and Langmuir models suggesting the ion exchange nature of the retention mechanism in most cases (E > 8 kJ/mol). Pseudo second-order model best described the kinetics of adsorption process. The adsorption mechanism was mainly monitored by ion exchange mechanism between exchangeable interlayer cations (Na) in the interstratified I/M and Cu2+ or Zn2+ metals from aqueous matrix. Further, the release of H+ ions from the edge of the layer structure in acidic environments promote the adsorption of heavy metals onto the surfaces interstratified I/M clay soils via electrostatic attraction. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).